2000
DOI: 10.1136/bjsm.34.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Isokinetic performance and shoulder mobility in elite volleyball athletes from the United Kingdom

Abstract: These elite volleyball players had a lower range of motion (internal rotation) and relative muscle imbalance in the dominant compared with the non-dominant shoulder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
106
3
16

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(134 citation statements)
references
References 24 publications
9
106
3
16
Order By: Relevance
“…The shoulder joint IR and ER movements were measured as the arms of the athletes were at 45° abduction in the scapular plane and the shoulders were at 90° flexion. This position was selected because the stress on the rotator cuff was minimal in this position compared with the position where the arms were at 90° abduction in the frontal plane (12,22). On the contrary, previous studies reported that this position was the most reliable position for assessing the shoulder IR and ER strength (14).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The shoulder joint IR and ER movements were measured as the arms of the athletes were at 45° abduction in the scapular plane and the shoulders were at 90° flexion. This position was selected because the stress on the rotator cuff was minimal in this position compared with the position where the arms were at 90° abduction in the frontal plane (12,22). On the contrary, previous studies reported that this position was the most reliable position for assessing the shoulder IR and ER strength (14).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, objective assessment of muscle strength in all athletes is crucial to the sportive success of athletes and prevention of injuries. Despite several studies in the literature exploring the upper extremity isokinetic strength profile in various sports fields such as swimming, handball, volleyball, tennis, water polo, cricket, judo, and basketball (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), no study has examined the upper extremity isokinetic muscle strength characteristic in weightlifters.…”
Section: Introductionmentioning
confidence: 99%
“…Os resultados do presente estudo não demonstraram diferenças estatisticamente significativas na velocidade angular de 180º/s, entretanto a 60º/s o MD apresentou valores médios significativamente superiores ao do MND, tanto para a musculatura RE como da RI na análise do PT. Estudos isocinéticos com atletas de modalidades esportivas assimétricas, como voleibol [17,[19][20][21][22][23], handebol [24,25], tênis [26][27][28], basebol [29,30] e polo aquático [31] também demonstraram que o MD apresenta valores maiores de PT dos RE e/ou RI. A utilização preferencial de um dos membros durante os principais movimentos de uma determinada prática esportiva faz com que haja um aumento da força muscular desse membro.…”
Section: /7unclassified
“…Apesar de escassa, a informação disponível relativamente ao efeito da idade aponta para padrões de evolução crescente dos torques máximos e da razão antagonista/agonista (7,20) . Adicionalmente, os resultados da investigação relativamente ao efeito das tarefas no perfil da força muscular isocinética sugerem uma adaptação funcional específica (9,38,39) . Deste modo, o objectivo do presente trabalho é o de avaliar e comparar o perfil das diferenças bilaterais de força e a razão isquiotibiais/quadriceps (I/Q) em diferentes desportos, idades, sexos e funções específicas.…”
Section: Introductionunclassified